Game Card Quartets for Increasing Numeracy Ability of Adding 1-10 for Intellectual Disability Students - Anton Cahyo Yuwhono; Wiwik Dwi Hastuti (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
This research was conducted with the aim to determine the effect of quartet card games towards the numeracy ability of adding 1-10 for intellectual disability students in the grade III SDLB. This study used an experimental research model pre-post design. The conclusion of this quasi-time-series experimental method is that the quartet card game can improve the numeracy ability of adding 1-10 for students with intellectual disability in the grade III SDLB.